Bilateral ganglioglioma of the trigeminal nerve in an 83‐year‐old man. Issue 2 (29th July 2013) - Hargus, Gunnar; Bink, Andrea; Nagel, Inga; Paulus, Werner; Harder, Anja
<x xml:space="preserve">Abstract</x> Gangliogliomas are well‐differentiated, mixed glio‐neuronal tumors of the CNS that are most frequently localized within the temporal lobe. In a minority of cases, gangliogliomas have been described in the brain stem where they may critically impinge anatomical structures. Rarely, ganglioglioma develop in cranial nerves, almost exclusively in the optic pathway, where they usually present as singular space‐occupying masses. Here, we report on an 83‐year‐old patient who presented with unusual symmetrical, bilateral gangliogliomas of the trigeminal nerves. These tumors showed an exophytic growth within the subarachnoid space toward the Gasserian ganglion and surprisingly appeared as isointense masses on T1‐ and T2‐weighted MRI. Due to their bilateral appearance, we performed array‐comparative genomic hybridization (aCGH) on the gangliogliomas to address the possibility of an underlying tumor syndrome in this patient. To our knowledge, this is the first case of bilateral ganglioglioma of the trigeminal nerve described so far.